PERAMALAN PRODUKSI DAN HARGA BAWANG PUTIH DI KABUPATEN LOMBOK TIMUR - Bq. Lisa Indrawati Putri; Anas Zaini; Anwar Anwar (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2022)
This study aims to: (1) analyze the pattern of development of garlic production and prices in East Lombok Regency. (2) Analyzing the most suitable quantitative forecasting method to predict the production and price of garlic in the next 5 years in East Lombok Regency. The data used in this research is secondary data. Then to process the data used time series forecasting method. The pattern of production and price data shows that there is an element of trend and after viewing the ACF and PACF, it shows that the data is stationary. The best forecasting for production uses the Single Exponential Smoothing method because it has the smallest error value. The results of the production calculation show that the MAD value is 13,414, the MSE value is 477,560,765, and the MAPE value is 17% and has an average production value of 6.088.9 ton. While the results of the price calculation, the MAD value is 4,090, the MSE value is 31,075,403, and the MAPE value is 8%, but the results of price forecasting are relatively constant at Rp. 40,000.